2016
DOI: 10.1039/c5nr09078d
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in polydopamine: an emerging soft matter for surface modification and biomedical applications

Abstract: After more than four billion years of evolution, nature has created a large number of fascinating living organisms, which show numerous peculiar structures and wonderful properties. Nature can provide sources of plentiful inspiration for scientists to create various materials and devices with special functions and uses. Since Messersmith proposed the fabrication of multifunctional coatings through mussel-inspired chemistry, this field has attracted considerable attention for its promising and exiciting applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
221
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 535 publications
(232 citation statements)
references
References 284 publications
2
221
0
2
Order By: Relevance
“…As shown in Figure 3, the results demonstrated the successful DA coating and NS formation. Because the surface hydrophilicity could influence the biological behavior of scaffold material, 46 water contact angle was measured subsequently. We found that the water contact angle was significantly lower on the PCL/ DA, PCL/NS0.5, PCL/NS1.0 and PCL/NS2.0 films than that on the pristine PCL (Figure 4), indicating that the surface hydrophilicity was obviously improved after DA coating and NS deposition, which might be helpful for better cytocompatibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3, the results demonstrated the successful DA coating and NS formation. Because the surface hydrophilicity could influence the biological behavior of scaffold material, 46 water contact angle was measured subsequently. We found that the water contact angle was significantly lower on the PCL/ DA, PCL/NS0.5, PCL/NS1.0 and PCL/NS2.0 films than that on the pristine PCL (Figure 4), indicating that the surface hydrophilicity was obviously improved after DA coating and NS deposition, which might be helpful for better cytocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…This result is caused by the reducibility of catechol group in DA, which could efficiently benefit for the silver reduction without destroy the primary scaffold structure. 18,46 To further investigate the surface chemical structure of PCL/NS after DA coating and NS deposition, the FTIR analysis was used. As shown in Figure 3, the results demonstrated the successful DA coating and NS formation.…”
Section: Discussionmentioning
confidence: 99%
“…DA can self‐polymerize at alkaline pH values to generate polydopamine (PDA) nanoparticles 11. Stable PDA nanoparticles can be easily produced with a simple and cost‐effective strategy and are completely composed of naturally occurring dopamine, and they have high biocompatibility and are suitable for biomedical applications 12.…”
Section: Introductionmentioning
confidence: 99%
“…The polydopamine layer not only readily adheres to most surfaces, but also provides a surface which allows various secondary reactions to take place and could therefore more easily enable the functionalization of material surfaces [22]. The reactions the catechol group of dopamine undergoes with metals, thiols, and amines has led to many research groups favouring the inclusion of dopamine when treating these surfaces [8,22,[24][25][26]36]. While many DOPA-functionalised grafting-to methods have proved successful on the specific surfaces listed above, researchers have encountered fouling when trying the same approach for hydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…et al [22,23]. Since then, a variety of dopamine-assisted grafting techniques and DOPA modified antifouling polymers have been tested to more securely attach antifouling polymers to substrate surfaces [23][24][25][26][27][28][29][30][31][32][33][34][35]. The polydopamine layer not only readily adheres to most surfaces, but also provides a surface which allows various secondary reactions to take place and could therefore more easily enable the functionalization of material surfaces [22].…”
Section: Introductionmentioning
confidence: 99%